The leadership of madrasah principals in improving teacher performance in West Sumatra - Hekyka, Suriya; Nurdin, Syafruddin; Sabri, Ahmad; Zalnur, Muhammad (Educenter : Jurnal Ilmiah Pendidikan, 2025)
This study explores the transformational leadership of madrasah principals and its impact on teacher performance in three institutions in West Sumatra: Madrasah Tsanawiyah Negeri (MTsN) Model Padang, MTsN 1 Kota Pariaman, and MTsN 4 Pasaman. The research addresses challenges such as the suboptimal application of transformational leadership in achieving transformative governance and the inadequate execution of managerial and supervisory functions. Employing a qualitative case study approach, data were collected through interviews, observations, and document analysis, and analyzed using data reduction, data display, and conclusion-drawing techniques. Data validity was ensured through extended engagement and consistent observation. The findings reveal that although transformational leadership practices are present, their implementation does not fully support transformative governance. Identified issues include teacher tardiness, insufficient administrative preparation, inappropriate teaching methods, weak classroom management, and the absence of evaluation and follow-up through remedial or enrichment programs. This study introduces the concept of Madrasah Head Leadership in 3 MTsN, which emphasizes a model of transformational leadership aligned with Ki Hajar Dewantara’s educational philosophy. This model focuses on openness to change and access to innovation in educational management. Through role modeling, motivation, and guidance, principals are expected to improve teacher performance and contribute to the overall development of the madrasah.